2022
DOI: 10.3390/agronomy12020541
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Soil Moisture Information in Developing Robust Climate Services for Smallholder Farmers: Evidence from Ghana

Abstract: In Ghana, most of the farmers are engaged in small-scale rainfed farming where the success is influenced by the prevailing weather conditions. Current Climate Information Services (CISs) only provide information on rainfall conditions to reduce their farming vulnerability to climate extremes. Access to other practical knowledge, such as soil moisture content would benefit farmers further in the decision-making process. This study aims to assess the role of soil moisture information in farmers’ agricultural dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…Climate services can include a range of services such as providing information on rainfall conditions, soil moisture and temperature patterns (Vaughan and Dessai 2014;Sutanto et al 2022). Small-scale producers often face challenges such as limited access to education, credit and agricultural services compared to large-scale commercial farmers (Sekaranom et al 2021).…”
Section: Climate Information Services (Also Referred To As Climate Se...mentioning
confidence: 99%
See 1 more Smart Citation
“…Climate services can include a range of services such as providing information on rainfall conditions, soil moisture and temperature patterns (Vaughan and Dessai 2014;Sutanto et al 2022). Small-scale producers often face challenges such as limited access to education, credit and agricultural services compared to large-scale commercial farmers (Sekaranom et al 2021).…”
Section: Climate Information Services (Also Referred To As Climate Se...mentioning
confidence: 99%
“…In the context of small-scale producers (SSPs), climate services refer to making available customized products and information that assist SSPs in adapting to and mitigating the impacts of climate change on their agricultural practices (Rubio-Martin et al 2021). For example, climate services can provide SSPs with information on suitable crops and planting dates based on climate projections, helping them optimize their yields and reduce risks (Sutanto et al 2022).…”
Section: Climate Information Services (Also Referred To As Climate Se...mentioning
confidence: 99%
“…Collaborating with policymakers, supporting research initiatives, and facilitating international collaboration can improve global efforts to address soil-related challenges. By prioritizing climate services for soil protection, stakeholders can ensure sustainable land use practices for the future and contribute to a healthier planet [145][146][147][148].…”
Section: Soil Management and Protectionmentioning
confidence: 99%
“…In their work to assess the role of SM information in agricultural decision-making by farmers in the Northern part of Ghana [6] concluded that SM information is critical to farming activities such as sowing and fertilisation. They observed that SM information is not available and accessible by farmers.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that SM information is not available and accessible by farmers. Unfortunately, there is a lack of dedicated SM monitoring networks in Ghana and, for that matter, most parts of Africa [3,6]. The Northern sector is one of the most water-limited regions of Ghana with a unimodal rainfall pattern (one rainy season) followed by a dry season [7].…”
Section: Introductionmentioning
confidence: 99%